Prescription and administration errors of antimicrobials in a pediatric inpatient unit - Gabriela M. MEIRA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To identify errors in the prescription and administration of antimicrobials in a pediatric inpatient unit of a public teaching hospital. Methods: This is a cross-sectional study with a quantitative approach in which a direct observation was performed of the preparation and administration of antimicrobials by daytime nursing technicians/assistants in patients hospitalized in the pediatric sector, as well as of their respective prescription with the prescribed antimicrobial item, in this order for ethical issues. The assessment was carried out with the help of two checklist forms, one of which was validated, following the safety protocol for the prescription, use and administration of medications by the Brazilian Ministry of Health. The data were tabulated in the Epidata 3.1 software and analyzed in SPSS 21.0, resulting in a sample of 174 administrations and prescriptions. Results: The most frequent inpatient diagnoses for using antimicrobials were diseases of the respiratory system (52.9%) followed by diseases of the urinary system (5.7%). The main types of prescription errors were absence of information about the diluent (97.1%), infusion rate (99.4%), incorrect dose (5.8%), and forbidden abbreviations (1.1%). In the administrations, the types of errors observed were the following: lack of patient identification by the professional (94.3%), lack of patient identification on the bed (12.1%), administration time (6.3%), and incorrect preparation and administration of the medication (1.1%). Conclusion: The main factors that led to errors in prescription and administration were evaluated, making it necessary to implement improvements in the electronic medical record with standardization for the dilution of the antimicrobials, issuing alerts in the prescription, integration of a clinical pharmacist in the team, effective communication, and coaching and permanent training.